Oxytocin (syntocinon) as stimulating factor for ovulation and uterine, mammary glands and placental development in white female mice - Hashim Ali, Israa (Tikrit Journal of Pharmaceutical Sciences, 2023)
The effect of oxytocin were studied as astimulating factor on ovulation, In this study30 female mice were carried out on 2-3 months,old with 24-30 g weight, They weredistributed of two,groups the control and,experimental, The white mice inexperimental,group were injected with adose of 10 IU/g of oxytocin at proestrusphase. The results showed that the pregnancy ratio in the experimental group wasabout 64% and the born ratio was about 59% which were higher than the controlgroup and the weight of newborn pups was more than the control. Histologically, Inthe ovarian section there was more follicles in different stages development inexperimental group when the endometrium of uterus was thicker than the control andabout the mammary gland section there was increased in alveolar surface area, Inaddition the results showed that oxytocin affected on placenta, It appears larger andthicker in the cross sections for experimental group.